Pengaruh Ekstrak Buah Pare (Momordica charantia L.) Terhadap Struktur Mikroskopis Hati Mencit (Mus musculus) - Suharsih, Suharsih (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2025)
Momordica charantia L. (bitter melon) contains various bioactive compounds that may affect internal organs, including the liver. This study aimed to examine the effect of bitter melon fruit extract on the microscopic structure of the liver in mice (Mus musculus). The research was conducted experimentally using a Completely Randomized Design (CRD) without factorial treatment, consisting of five groups: untreated control, aquadest control, and treatment groups receiving bitter melon extract at doses of 750 mg/kg BW, 1500 mg/kg BW, and 2250 mg/kg BW, with five replications each. The extract was administered orally using a gavage needle at a volume of 0.1 mL/10 g BW daily for 40 days. The results showed that the extract did not significantly affect body weight or liver weight. Microscopically, the 750 mg/kg BW and 1500 mg/kg BW doses did not alter liver histology compared to the control, while the 2250 mg/kg BW dose caused histological damage in the form of hepatocyte steatosis. Macroscopically, the liver in the highest dose group appeared paler than in the control group, although the overall shape remained normal in all groups. It can be concluded that high doses of bitter melon extract may induce microscopic liver changes, whereas lower doses do not exhibit hepatotoxic effects.